Synthesis, crystal structure and magnetic properties of R11Ni60C6 (R = Tb, Dy) compounds. (November 2018) - Levytskyi, V.; Isnard, O.; Babizhetskyy, V.; Kotur, B.
Abstract: Two metal-rich intermetallic carbides R11 Ni60 C6 were synthesized using arc melting followed with heat treatment of the alloys at 800 °C for 6 months. Crystal structure of both compounds has been refined using powder XRD, including atomic coordinates with their isotropic displacement parameters. R11 Ni60 C6 refer to Yb11 Ni60 C6 structure type, space group Im 3 ¯ m ; for R = Tb: a = 12.50393 (6) Å, for R = Dy: a = 12.49285 (6) Å. New ternary carbide Tb11 Ni60 C6 displays ferromagnetic-like magnetic behavior at temperatures below T C = 6.6 K Dy11 Ni60 C6 also presents magnetic ordering at low temperature ( T C = 4.8 K) indicating the absence of Ni magnetic moment. Evaluated effective magnetic moments correspond to respective values of R 3+ ions in these compounds. Graphical abstract: Image 1 Highlights: New Tb–Ni–C intermetallic carbide has been synthesized. Crystal structure of R11 Ni60 C6 (Yb11 Ni60 C6 -type) is considered as CaCu5 -derivative. R11 Ni60 C6 (R = Tb, Dy) display low-temperature ferromagnetic ordering (TC < 10 K). Effective paramagnetic moment of R11 Ni60 C6 (R = Tb, Dy) is close to μeff /R 3+ value.